Michael Oakeshott and Liberalism Revisited
X, 387 p. 1 illus.
Keywords: This book assesses the significance of Michael Oakeshott’s political philosophy and his relationship to liberalism, both in theory and in practice. The essays coverage a range of different topics, including Oakeshott in relation to other thinkers like Hobbes, Strauss, Houellebecq, Berlin, and Aristotle; Oakeshott’s thought in the context of countries like China and Poland; Oakeshott’s thought on legal theory and policies relating to technology; and Oakeshott’s liberal theory on its own. In the thirty-five years since Oakeshott died, interest in his work continues to grow. How Oakeshott’s thought illuminates issues that have persisted since his time and have taken on new dimensions is an important investigation in the history of political thought. Eric S. Kos is a recently retired professor of political science from Siena Heights University. He is the editor of Michael Oakeshott on Authority, Governance, and the State (Palgrave Macmillan, 2019) and Oakeshott’s Skepticism, Politics, and Aesthetics (Palgrave Macmillan, 2022). He is also a charter member of the Michael Oakeshott Association, of which he was the president from 2015 to 2017 and a secretary from 2011 to 2015 and from 2019 to present.